Decorin suppresses tumor cell growth by activating the epidermal growth factor receptor. - Moscatello, D K (1998)
Decorin, a small leucine-rich proteoglycan, is capable of suppressing the growth of various tumor cell lines when expressed ectopically. In this report, we investigated the biochemical mechanism by which decorin inhibits cell cycle progression. In A431 squamous carcinoma cells, decorin proteoglycan or protein core induced a marked growth suppression, when either exogenously added or endogenously produced by a transgene. Decorin caused rapid phosphorylation of the EGF receptor and a concurrent activation of mitogen-activated protein (MAP) kinase signal pathway. This led to a protracted induction of endogenous p21, a potent inhibitor of cyclin-dependent kinases, and ultimate cell cycle arrest. Biglycan, a related proteoglycan, had no effect. Moreover, decorin activated the EGF receptor/MAP kinase/ p21 axis in cell lines of various histogenetic backgrounds. These results provide the first evidence that EGF and decorin converge functionally to regulate the cell cycle through activation of a common pathway which ultimately leads to growth suppression.